PERAN INTERAKSI SEKOLAH LUAR BIASA (SLB) PANAM MULIA BAGI ANAK DI KELURAHAN TAMAN KARYA KECAMATAN TAMPAN SELAMA PANDEMI COVID-19 - Achmad Hidir; Resdati; Alvin Brain Sinaga; Fadhlan Arifin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Parents are one of the roles that each community has. But not all parents have children with perfect physical conditions. Most parents send their children with special needs not to put them in public schools but to special schools or commonly known as special schools. SLB is a school for children with special needs so that they can carry out or play with their peers at school as in other public schools. The research in this article is studied to find out how much parents or trustee parents and their teachers were involved in increasing the effectiveness of learning at SLB Panam Mulia during the Covid-19 pandemic. The research method used was a descriptive qualitative research approach. Data collection was included in the form of observations, interviews, and documentation. The subjects in this study were concerned with the parents or trustee parents of the students. The purpose of using this method was how the parents or trustee parents of the students and the teachers were concerned to provide the information to overcome the changes in the learning system for special schools during the Covid-19 pandemic so that teaching and learning activities remained effective. And SLB students continued to receive good quality learning services and provide the information related to the analysis of the social impacts experienced by all SLB components regarding the systematic changes in learning during the Covid-19 pandemic.